(untitled) (Medico Legal Update, 2020)
Background- Empowering employees is an essential factor to reduce workplace stress, whereas its role in enhancing job satisfaction among employees is through perceived job obligation, and reducing stress. Aim- The present study endeavored to determine the relationship between Psychological Empowerment and Job Satisfaction among nurses. Methods and Materials- Cross-sectional, descriptive and correlational study design carried out for a period from 5th of September/2017 till 30th of May/2018 at five hospitals in Mosul/Iraq. Non-probability sampling technique and accidental sampling method were depended to select (317) nurse as a sample of the study. An interview was the method through which data were gathered. Two instruments were used to collect data; Psychological Empowerment questionnaire “PE”, and Minnesota Job Satisfaction questionnaire “JS”. Mean, Standard deviation and stepwise regression analysis were used to present the findings of the study. Findings- Total Psychological Empowerment and Total Job Satisfaction and their domains had an acceptable level, from another side, Total Psychological Empowerment and its domains had significant relations with Total Job Satisfaction and its domains